Nursing management of patients with relapsed or refractory classical Hodgkin's lymphoma treated with sintilimab (信迪利单抗疗治疗复发或难治性霍奇金淋巴瘤的专科护理) - KUANG Meiling (邝梅玲); TAN Xingxing (谭星星) (中西医结合护理)
This paper reviewed the clinical data of 54 patients with relapsed or refractory classical Hodgkin's lymphoma treated with sintilimab, and summarized the key points of specialized nursing. In the treatment of refractory classical Hodgkin's lymphoma by sintilimab, nursing measures should be carried out, such as standardization of drug preservation, configuration and infusion operation, observation on adverse reactions, implementation of specialized nursing measures timely, and enhancement of psychological care. The comprehensive nursing management is effective to reduce the risk of sintilimab-induced adverse reactions, relieve patients' negative emotions and increase treatment compliance of patients. (本文回顾性分析54例经信迪利单抗治疗的复发或难治性霍奇金淋巴瘤患者的临床资料, 总结专科护理要点。在信迪利单抗治疗复发或难治性霍奇金淋巴瘤过程中, 严格执行药物保存、配置及输注操作规范, 严密观察不良反应并及时采取积极有效的专科护理措施, 做好专科心理护理, 可减少信迪利单抗相关不良反应的发生风险, 减轻不良反应对患者的负面影响, 缓解患者焦虑抑郁情绪, 增加患者治疗依从性, 对患者顺利完成抗肿瘤治疗及提高疗效有积极意义。)